MAJOR AMERICAN NEWSPAPERS AND THEIR COVERAGE OF THE 1991 IRAQI KURDISTAN UPRISING: A STUDY OF EVENTS AND OFFICIAL POSITIONS - Taher, Ayhan (Humanities Journal of University of Zakho, 2025)
The March 1991 revolt in Iraqi Kurdistan marked a watershed moment in the Kurdish people's battle for national rights. The rebellion began in the aftermath of the Second Gulf War, taking advantage of the Iraqi army's vulnerability following its defeat and popular anger with Saddam Hussein's regime, coinciding with an uprising in southern Iraq. The revolt was marked by widespread participation from diverse elements of the Kurdish people, who gained control of the majority of Kurdish cities and territories, demanding the overthrow of Saddam Hussein's dictatorship and the establishment of Kurdish autonomy. Major American publications provided significant coverage of the March rebellion, which focused on reporting events in Kurdistan and Iraq. These newspapers sought to present a realistic picture of what was happening on the ground, shedding light on the political positions of the US government and Kurdish leaders. This media coverage provided an important account of the developments of the uprising and its international repercussions, highlighting the important role of journalism in documenting historical events.